Physicochemical characterization of seven fruits from the Cerrado - Renato D’Elia Feliciano; Fernanda Sviech; Ana Silvia Prata; Alexander Vicente Christianini (Brazilian Journal of Food Technology)
Abstract Many species of woody plants from the Cerrado (tropical savanna in central Brazil) can produce fleshy fruits. Still, their chemical composition is primarily unknown, due to the lack of commercial interest or regular access to said species. The present study provides the centesimal composition of seven native fruit species from the Cerrado: Lobeira (Solanum lycocarpum Solanaceae), Angelim-rasteiro (Andira humilis Fabaceae), Abacaxi-do-Cerrado (Ananas ananassoides Bromeliaceae), Araçá-do-campo (Psidium grandifolium Myrtaceae), Caraguatá (Bromelia balansae Bromeliaceae), Pequi (Caryocar brasiliense Caryocaraceae) and Araticum (Annona crassiflora Annonaceae). Fruit samples were collected from protected areas of the Cerrado in southeastern Brazil. The centesimal composition was analyzed without distinguishing between flesh, seeds, and peel. All fruits presented a moisture content ranging from 55.2% to 83.0%, and low ash contents (less than 4.5%). The Lobeira, the Angelim-rasteiro, and the Abacaxi-do-Cerrado stood out for having a higher percentage of protein (15.9%, 16.2%, and 10%, respectively). In contrast, the Araçá-do-campo, the Caraguatá, and the Araticum had high levels of carbohydrates (23.8%, 21.6% and 35.9%, respectively). Results indicate these fruits’ potential for the food industry, as well as for the development of new food products.